2015
DOI: 10.1093/mnras/stv2812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the sources of reionization on 21-cm redshift-space distortions

Abstract: The observed 21-cm signal from the epoch of reionization will be distorted along the line-of-sight by the peculiar velocities of matter particles. These redshift-space distortions will affect the contrast in the signal and will also make it anisotropic. This anisotropy contains information about the cross-correlation between the matter density field and the neutral hydrogen field, and could thus potentially be used to extract information about the sources of reionization. In this paper, we study a collection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 84 publications
(125 reference statements)
2
52
0
Order By: Relevance
“…Note thatMajumdar et al (2016b) has demonstrated the evolution of the EoR 21-cm signal using a similar phase space of monopole and quadrupole moments of the redshift space 21-cm power spectrum.MNRAS 000, 000-000(0000)…”
mentioning
confidence: 99%
“…Note thatMajumdar et al (2016b) has demonstrated the evolution of the EoR 21-cm signal using a similar phase space of monopole and quadrupole moments of the redshift space 21-cm power spectrum.MNRAS 000, 000-000(0000)…”
mentioning
confidence: 99%
“…If the distribution and the properties of the reionization sources change, the topology of the ionization field will also change and one would expect then the phase difference between the matter and the H i field to also change, which it turn should have a signature in the quadrupole moment. To test whether this idea can be used to distinguish between different reionization sources using the nature and amplitude of P s 2 , Majumdar et al (2016) simulated a collection of reionization scenarios considering various degrees of contribution from different kinds of reionization sources. The reionization scenarios they considered include ionizing photon contribution from the usual UV photon sources hosted by the halos with mass 10 9 M , a uniform ionizing background generated by hard X-ray sources, a local uniform ionizing background generated by soft X-ray sources (limited by the mean free path of soft X-ray photons), various combinations of all of these three contributions, reionization driven by quasar like very strong sources located around the most massive halos etc.…”
Section: During the Eormentioning
confidence: 99%
“…This effect is called the redshift-space distortion (RSD) (e.g. Jensen et al 2013;Majumdar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other work has focused specifically on using the anisotropy generated in the 21-cm signal by the RSDs to separate astrophysical and cosmological affects (e.g. Shaw & Lewis 2008;Shapiro et al 2013;Majumdar et al 2015).…”
Section: Introductionmentioning
confidence: 99%